Short-term effect of low-intensity pulsed ultrasound on an ex-vivo 3-D tooth culture - Al-Daghreer, S.; Doschak, Michael; Sloan, A.; Major, P.; Heo, G.; Scurtescu, C.; Tsui, Y.; El-Bialy, T. (Elsevier Inc., 2013)
We investigated the short-term effect of LIPUS on human dentin-pulp complex in vitro. We collected sixty-three premolars from patients who needed the extraction. The premolars were sectioned transversely into 600-µm-thick slices, and then divided into five groups according to LIPUS application time (control, 5, 10, 15 and 20 min). LIPUS transducer produced an incident intensity of 30 mW/cm2. After 24 h, tissue was harvested for histomorphometrical analysis and RT-PCR (Genes of interest: Collagen I, DMP1, DSPP, TGF ß1, RANKL and OPG). Histomorphometric analysis showed no significant difference among the five groups in the odontoblast count and predentin thickness. RT-PCR demonstrated no expression of TGF ß1, low amounts of DSPP, a twofold increase in collagen I expression in the 5- and 10-minute LIPUS groups and a threefold increase in DMP1 expression in the 10-minute LIPUS group. LIPUS application was stimulatory to the dentin-pulp complex in vitro and increased the expression of collagen I and DMP1.